2017
DOI: 10.1111/jdv.14664
|View full text |Cite
|
Sign up to set email alerts
|

Koebner's sheep in Wolf's clothing: does the isotopic response exist as a distinct phenomenon?

Abstract: Until 1995, a case of psoriasis developing within the dermatome of a healed herpes zoster was taken as a Koebner phenomenon. In this year, however, the term 'isotopic response' was introduced by Wolf et al. to describe 'the occurrence of a new skin disorder at the site of another, unrelated and already healed skin disease', thus appearing 'on apparently unaffected and healthy skin'. Initially, the term was mainly related to herpes zoster, but today the name 'Wolf's isotopic response' is used to include a pleth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…Eczema is included in the fourth category, along with a number of other conditions. By contrast, the cases of NE on the scar sites in the current study suggest that KR can result in NE, because injured skin is not normal and thus is susceptible to developing other lesions 2 . A recent study reported that out of 1662 patients who had undergone breast reconstruction, 48 developed NE, 3 which both occurred in periwound and nonperiwound regions, and in some of the cases, the lesions developed on the operation scar.…”
Section: Figurecontrasting
confidence: 72%
“…Eczema is included in the fourth category, along with a number of other conditions. By contrast, the cases of NE on the scar sites in the current study suggest that KR can result in NE, because injured skin is not normal and thus is susceptible to developing other lesions 2 . A recent study reported that out of 1662 patients who had undergone breast reconstruction, 48 developed NE, 3 which both occurred in periwound and nonperiwound regions, and in some of the cases, the lesions developed on the operation scar.…”
Section: Figurecontrasting
confidence: 72%
“…The conspicuous colocalization of EG‐LSA with pre‐existent mosaic hypermelanosis may be best explained as a Koebner phenomenon 1 . The term ‘Wolf’s isotopic response’ should be avoided for such colocalization since, in our view, this term reflects a historical error 6 …”
Section: Figurementioning
confidence: 99%
“…4 Actually, the term Wolf's isotopic response is not approved by all physicians and it is till matter of discussion if this phenomenon should be classified as a variant of the Koebner (isomorphic) response. 5 Its pathogenesis is currently unknown. Some authors suggested that it might be due to viral particles that remain in the tissue and are responsible for the onset of the subsequent disease.…”
Section: Annular Elastolytic Giant Cell Granuloma Following Herpes Zomentioning
confidence: 99%